Improving Students Religious Understanding Through the Imtaq Program - Rizaldi, Adli; Syafe'i, Imam; Yuberti, Yuberti (Universitas Islam Negeri Raden Intan Lampung, 2024)
The integration of the values of faith and piety in the education curriculum is very important to shape the character of students who are more religious and noble. This study aims to determine the Implementation of the Imtaq Program in Improving the Religious Understanding of State Junior High School Students in Bandar Lampung City. Implementation is an action, application or implementation of a plan that has been prepared carefully and in detail to achieve the objectives of the activity to run effectively. Imtaq is a tool that will guide education towards its original goal of producing a knowledgeable generation of believers who are able to compete successfully and fear Allah SWT. Religious understanding is a learning process in which a person is able to understand the religious values he adheres to so that he can practice these values in his attitude and behaviour. This research uses a qualitative approach with data collection methods of observation, interviews, and documentation. The results of this study show that the Imtaq program at school has a positive impact because it succeeds in providing knowledge, experience, and religious practice as well as being a value of worship for students. The Imtaq program is able to touch values that can be used for real life for the benefit of students themselves and in social life. The Imtaq program is able to create peaceful situations and conditions, prevent students from negative associations, and fortify them with faith and piety.